Allowable Bending Properties of Machine-Graded Korean Yellow Poplar Lumber - Da-Bin Song; Kug-Bo Shim; Sang-Joon Lee; Keon-Ho Kim; Chul-Ki Kim (BioResources, 2024)
This study was conducted to investigate the feasibility of using yellow poplar as a structural member by determining allowable bending properties. Full-size lumber was classified by machine grading and the knot diameter ratio on the wide surface of lumber. The majority of machine grades of yellow poplar lumber with a cross-section of 38 × 89 mm2 were E8, E9, and E10. It was confirmed that the size of the knot diameter ratio tended to be smaller for higher machine grades. In the lowest grade, E8, of most machine grades, the allowable bending strength was lower than the corresponding design value in Korean standards. Application of 0.5 knot diameter ratio to the E8 grade lumber increased the bending strength to 3 MPa of the allowable value to suit the design value. All the allowable modulus of elasticities values of the majority of machine grades were higher than the design values. From the results of this study, it was expected that Korean yellow poplar could be utilized for structural bending members.